INTERNALISASI KESADARAN BERAGAMA ISLAM BERBASIS BUDAYA SEKOLAH : STUDI FENOMENOLOGIS DI SMP MUHAMMADIYAH 9 SURABAYA - Salsabila Arum Az Zahro Putri; Moch. Charis Hidayat; Ika Puspitasari (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2026)
Religious awareness is a crucial aspect of adolescent character development, particularly during the identity formation phase influenced by technological advancement and social environments. This study aims to examine to the process of internalizing Islamic religious awareness among students at SMP Muhammadiyah 9 Surabaya, including the forms of internalization, the role of Islamic Religious Education teachers and the school environment, as well as supporting and inhibiting factors. This research employed a qualitative method with a phenomenological approach. Data were collected through participant observation, in-depth interviews with students, Islamic Religious Education teachers, and the principal, as well as documentation of religious activities. The findings reveal that the internalization process occurs through three stages: value transformation, value transaction, and transinternalization. The process is strengthened by contextual Islamic learning, teacher role modeling, and the habituation of religious practices within the school culture. The study highlights that a religious school ecosystem and sustainable religious programs serve as key supporting factors, while social media influence, limited parental involvement, and peer pressure act as inhibiting factors.These findings enrich the discourse on religious value internalization by emphasizing the role of school culture ecosystems and students' social dynamics in fostering self-regulated religious awareness.